2010
DOI: 10.1093/humrep/deq117
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcomes after transfer of vitrified blastocysts

Abstract: No adverse neonatal outcomes were observed in children born after transfer of vitrified, as compared with fresh blastocysts or after transfer of slow-frozen early cleavage stage embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 26 publications
6
77
0
11
Order By: Relevance
“…Deliveries included all live born babies and stillborns after 28 weeks of gestation. Perinatal mortality included mortality in live borns within 7 days of age and stillborns after 28 weeks of gestation (Wikland et al, 2010).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Deliveries included all live born babies and stillborns after 28 weeks of gestation. Perinatal mortality included mortality in live borns within 7 days of age and stillborns after 28 weeks of gestation (Wikland et al, 2010).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Although vitrification is now used widely in assisted reproduction treatment (ART) clinics, there are still concerns regarding the safety of vitrification. Most published reports looking at the neonatal outcomes after transfer of vitrified embryos have used blastocyst-stage embryos (Takahashi et al, 2005;Mukaida et al, 2009;Wikland et al, 2010). Reported data on children born after transfer of Day 3 vitrified embryos are relatively rare (Rama Raju et al, 2009;Kato et al, 2012;Shi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Wikland et al, no difference in birth weight was observed after the transfer of vitrified blastocysts or slow-frozen early cleavage stage embryos [31]. The blastocyst culture itself has been found to have an impact on the birth weight of newborns, complicating the comparison of two cryopreservation techniques using embryos from different stages [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…We agree that in such a scenario the use of a selection method cannot increase (but could decrease) the live birth rate per stimulated IVF cycle when all embryos are serially transferred (albeit potentially reducing the time to first delivery). Indeed, there may be an argument for vitrification of all embryos without fresh transfers, considering potentially superior peri-natal outcome of births resulting from transfer of thawed blastocysts (Wikland et al, 2010). In that study, more singletons born after transfer of fresh blastocysts were small for gestational age compared with singletons born after transfer of vitrified blastocysts.…”
mentioning
confidence: 87%